1985
DOI: 10.1017/cbo9780511564451
|View full text |Cite
|
Sign up to set email alerts
|

Creep of Crystals

Abstract: This textbook describes the physics of the plastic deformation of solids at high temperatures. It is directed at geologists or geophysicists interested in the high-temperature behaviour of crystals who wish to become acquainted with the methods of materials science in so far as they are useful to earth scientists. It explains the most important models and recent experimental results without losing the reader in the primary literature of materials science. In turn the book deals with the essential solid-state p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
315
2
6

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 929 publications
(334 citation statements)
references
References 0 publications
11
315
2
6
Order By: Relevance
“…The yield points cannot be detected here because they lie at such low confining pressures that stage I cannot be clearly observed. Note that the shear moduli for NaC1 (26 GPa) and Cu3Au (45 GPa, calculated from the values for Cu and Au weighted by the appropriate stoichiometry) are quite similar, and that the pressure dependence of the shear modulus is higher for NaCI than for Cu3Au (2.1 versus 1.6) (Poirier, 1985). The shear moduli should thus become equal around 1.4 GPa.…”
Section: Figurementioning
confidence: 92%
“…The yield points cannot be detected here because they lie at such low confining pressures that stage I cannot be clearly observed. Note that the shear moduli for NaC1 (26 GPa) and Cu3Au (45 GPa, calculated from the values for Cu and Au weighted by the appropriate stoichiometry) are quite similar, and that the pressure dependence of the shear modulus is higher for NaCI than for Cu3Au (2.1 versus 1.6) (Poirier, 1985). The shear moduli should thus become equal around 1.4 GPa.…”
Section: Figurementioning
confidence: 92%
“…The first basis for this has been given by (Frost and Ashby, 1982), who have shown that choosing a proper normalization for stress and temperature (usually Page 4 of 31 A c c e p t e d M a n u s c r i p t 4 stress is normalized to the shear modulus and temperature to the melting temperature although Poirier (1985) emphasizes rightly that this choice is not unique), allows the construction of deformation-mechanism maps. A possible inference from these maps is that under the same normalized conditions, materials belonging to the same isomechanical group would exhibit the same dominant deformation mechanism.…”
Section: (R2) For Thismentioning
confidence: 99%
“…Polygonization often can be identified by occurrence of more nearest-neighbor grains with small misorientations than would occur randomly in a sample. (Poirier ( 1985 ) distinguished between the formation of new grains by subdividing, which he called "creep polygonization", and the refinement of this structure by further deformation, which he called "rotation recrystallization". Here I use "polygonization" to refer to both.…”
Section: Journal Qf Glaciologymentioning
confidence: 99%